SEMINOMA ANAPLASTIK DENGAN YOLK SAC TUMOR TESTIS (MIXED GERM CELL TUMOR TESTIS) - Loho, Lily (Jurnal Biomedik : JBM, 2012)
Abstract: Testicular cancer is relatively rare, accounting for less than 1% of malignant tumors affecting men. More than 90% of these tumors are of germ cell origin and most of them are found in young men between the ages of 15-34 years. Germ cell tumors are divided into seminoma and nonseminoma tumors. The seminoma makes up 30-40% of all testicular tumors. An anaplastic seminoma is a classic type of seminoma that has three or more mitosis under the high power microscopic field, combined with other morphologic criteria such as nuclear hyperchromasia, greater nucleolar sizes, pleomorphism, and an amount of necrosis. We reported a case of a 38-year-old male that was clinically diagnosed with a left testicular tumor and with an elevated alpha fetoprotein (AFP) and β human chorionic gonadotropin (β HCG) serum. The histopathological diagnosis was an anaplastic seminoma with a yolk sac tumor (YCT), i.e. a mixed germ cell tumor. Keywords: seminoma, testicular tumor, yolk sac tumor.   Abstrak: Kanker testis relatif jarang,  <1% dari semua kanker ganas pada laki-laki. Lebih dari 90 persen jenis tumor ini berasal dari sel germinal dan umumnya menyerang laki-laki muda berusia 15-34 tahun. Tumor sel germinal dibagi atas dua jenis: seminoma dan non seminoma. Jenis seminoma terdapat pada 30-40% dari seluruh tumor testis. Seminoma anaplastik adalah seminoma dengan ciri klasik mikroskopik berupa adanya tiga atau lebih sel-sel mitosis per lapangan pandang besar, disertai terdapatnya kriteria morfologik lain seperti inti sel hiperkromatik, anak inti berukuran besar, pleomorfik, dan terdapatnya sejumlah nekrosis. Kami melaporkan kasus seorang laki-laki berusia 38 tahun dengan diagnosis klinis tumor testis kiri disertai peningkatan kadar alfa feto protein (AFP) dan β human chorionic gonadotropin (β HCG) serum. Diagnosis histopatologik ialah  seminoma anaplastik dengan tumor yolk sac (YCT), yaitu tumor sel germinal campuran. Kata kunci: seminoma, tumor testis, tumor yolk sac.